Pedal forces during the bmx and track sprint cycling start - Janssen, I.; Cornelissen, J. (ISBS Proceedings Archive (Michigan), 2017)
During the start of a BMX and sprint track cycling race, a high amount of pedal force is required to accelerate the bike. The purpose of this study was to quantify the effective force (Fe), resultant force (Fr) generated in the lead and trail leg in BMX and sprint track cyclists when performing a standing start. Instrumented force pedals quantified the generated forces from each leg separately. Significantly greater Fe was generated with the lead leg than the trail leg (p=0.011) and a higher Fe and Fr resulted in a faster time of the first pedal stroke. There was no significant difference found in any of the pedal force variables between the BMX and track cyclists (p=0.750). Additionally, cyclists with greater Fe and Fr in the trail leg produced greater maximum power output on the Wattbike test. These data provide further insight into how cyclists propel the bike from a still position.